A cross-sectional study on the coverage and utilization of sanitary latrine in rural field practice area of a tertiary care hospital in Southern Karnataka, India - M. P., Sheethal; S. K., Shashikantha (International Journal Of Community Medicine And Public Health, 2017)
Background: Sanitation is one of the basic determinants of quality of life and human development index. Open air defecation has dire health impacts. Objective of the study is to determine the sanitary latrine coverage, use and factors influencing its use in a rural community. Methods: This cross sectional study was conducted in the rural field practice area for 3 months. Around 259 households were included for the present study. Data was collected by house to house visit in the selected villages using a pretested structured questionnaire. The infrastructure of the sanitary latrine was observed and noted. Data was entered in excel sheet and analysed using epi-data software. Results: Sanitary latrine was present in 213 houses (82%) and rest 18% practiced open air defecation. The average duration of use of sanitary latrine was 6.33±6.03 years. Nearly 90% (189) of the latrines were private latrines, majority of the sanitary latrine were pucca with adequate lighting and good ventilation. Conclusion: Majority of them were using latrines, only 18% of them practiced open air defecation. But among the houses with latrine, more than half of the latrines did not have water facility and soap in the latrine. Majority of them felt that safety was the most common advantage of having a latrine.